Best Answer

-2x-10y-12+3xy=4

Put all x's to the other side and the ones with y's on the other:

-10y+3xy=4+2x+12

-10y+3xy=16+2x

Now you factor a y from the side with the y's:

y(-10+3x)=16+2x

Divide both sides by (-10+3x):

y=(16+2x)/(-10+3x)

Q: How do you solve -2x-10y-12 and 3x y equals 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x=12 3x/3=12/3 x=4

3x+4 = 2x-3 3x-2x = -3-4 x = -7

x=4 x=4

12/3 = 4

You don't, unless you know either the value of x or what the expression equals.

Related questions

2y-3x=4

3x=12 3x/3=12/3 x=4

3x + 4= 7 3x= 7-4 3x/3 = 3/3 x=1

3x+4 = 2x-3 3x-2x = -3-4 x = -7

3x+4=10 To solve: 3x+4=10 3x=6 x=2

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

x=4 x=4

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

x = 6

12/3 = 4

4+3x-27=-12 To solve it... 3x= -12-4+27 3x= 11 x= 11/3 x= 3.666

You don't, unless you know either the value of x or what the expression equals.